Liver Tumor Characterization – Comments and Illustrations Regarding Guidelines - Dietrich, C. F. (Ultraschall in der Medizin - European Journal of Ultrasound, 2012)
Contrast-enhanced ultrasound (CEUS) is a well established diagnostic imaging technique for a variety of indications and applications. One of the most important applications is in the liver where it is frequently a first-line technique for the detection and diagnosis (characterization) of focal liver lesions (FLLs). In this setting the accurate differentiation of benign lesions from malignant lesions is critical to ensure that the patient undergoes the appropriate therapeutic option. In this article the role of CEUS in the characterization of FLLs is described on the basis of recently published guidelines, in particular in terms of the enhancement patterns of the most common FLLs, e. g. hemangioma, focal nodular hyperplasia, hepatocellular adenoma and their differentiation from malignant lesions.
Keywords: diagnosis; characterization; metastases; hepatocellular carcinoma; focal nodular hyperplasia; hemamgioma; microbubble